PENDAMPINGAN PENELITIAN DAN PENULISAN KARYA ILMIAH PADA KELOMPOK SISWA PESERTA PENGEMBANGAN DIRI SAINS SMP PUSRI PALEMBANG - Atina Atina; Ita Emilia; Dian Mutiara (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
This dedication activity was carried out in Pusri Junior High School (SMP Pusri) of Palembang and PGRI Palembang University in May - July 2019. Pusri Junior High School plans to send representatives of its students to participate in the Olimpiade Penelitian Siswa Indonesia (OPSI) in 2019 organized by the Directorate of Junior High School Ministry of Education and Culture Development. But the school experienced problems in terms of research assistance and writing of research results in the form of scientific work / scientific articles. This is due to the lack of equipment owned by schools and the lack of teacher's ability in writing scientific papers. The object of devotion is the Pusri Junior High School students participating in the “Pengembangan Diri (PD)” activities of 3 people (1 group). The mentoring activities are focused on research assistance until data and analysis are obtained as well as writing research results in the form of scientific articles. The dedication activity ended after the creation of scientific papers in accordance with the provisions of OPSI 2019 and Pusri Junior High School student representatives can register to be OPSI 2019 participants. The mentoring process can be completed on time and the Pusri Junior High School student representatives can register as 2019 OPSI participants in August 2019 and the difficulties of the school can be resolved.